Teaching and learning foreign languages for special purposes at technical universities - Gajewska-Skrzypczak, Iwona (Glottodidactica, 2010)
The main aim of my work is to explore the options and problems connected with teaching and learning ESP at technical universities. I tried to answer questions concerning the right choice of methods enabling students to develop their language skills effectively with an emphasis on professional language competence.